Secang wood (Caesalpinia sappan L.) nanoemulgel activity as antiaging through suppressing the MMP-1 expression and the collagen degradation - Ni Putu Linda Laksmiani; Ni Putu Eka Leliqia; Ni Luh Putu Vidya Paramita; I Gusti Kamasan Nyoman Arijana; Ni Putu Ayu Dewi Wijayanti; Putu Ivan Adiwibawa; I Made Harimbawa Putra; I Putu Ari Anggara Catur Pratama (GarVal Editorial Ltda., 2022)
Context: Aging is closely related to reactive oxygen species (ROS). ROS increases the collagenase enzyme (MMP-1) levels and collagen degradation that causes skin wrinkling. Secang wood (Caesalpinia sappan L.) containing brazilin and brazilein has been shown to have photoprotective and antioxidant properties. Aims: To evaluate the activity of C. sappan nanoemulgel as antiaging agent against the target protein, matrix metalloproteinases (MMPs), especially MMP-1, MMP-3, and MMP-9 by in silico assay and using in vivo assay through MMP-1 and collagen expression parameter. Methods: C. sappan nanoemulgel was made by mixing the gel base with C. sappan nanoemulsion from heartwood extract. The C. sappan nanoemulsion was formulated using the Self Nanoemulsifying Drug Delivery System method. In vivo testing was conducted with a post-test-only control group design and used male Wistar rats. MMP-1 expression was examined using immunohistochemical techniques, and the amount of dermal collagen was observed with Picro Sirius Red staining. In silico assay using a computational method with Autodock 4.2 program. Results: C. sappan nanoemulgel concentrations of 0.0625, 0.125, and 0.25% obstruct the expression of MMP-1 and collagen degradation. The bond energy value to MMP-1, MMP-3, and MMP-9 were -8.04, -10.40, and -8.70 kcal/mol (for brazilin); -8.82; -10.99, and -8.51 kcal/mol (for brazilein). Conclusions: Nanoemulgel containing C. sappan nanoemulsion has a potential activity as an antiaging agent by repressing MMP-1 expression and dermal collagen degradation. C. sappan nanoemulgel 0.25% showed the best result as antiaging. Brazilin and brazilein from C. sappan inhibit the MMP-1, MMP-3, and MMP-9 by in silico assay.